The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.32362/2410-6593-2020-15-3-31-38
|View full text |Cite
|
Sign up to set email alerts
|

An effective method for preparation of high purity oligohexamethylene guanidine salts

Abstract: Objectives. Given that microorganisms can become resistant to certain groups of drugs and considering also their ability to form biofilms, the development of new drugs that are active against adapted microflora is required. This study focused on the development of a new method for the synthesis of a promising compound, the branched hydrosuccinate oligohexamethylene guanidine (OHMGsucc), with high purity that meets the standards of the 14th edition State Pharmacopeia of the Russia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…The observed effect of inhibition of biofouling in the case of DNDamine coating seems to have the same mechanism as that observed for polycationic polymers -guanidine derivatives, which are known antiseptic agents [42][43][44]. In the case of the latter, close contact of a substance with a high density of positively charged groups with cell walls…”
Section: Discussionsupporting
confidence: 56%
“…The observed effect of inhibition of biofouling in the case of DNDamine coating seems to have the same mechanism as that observed for polycationic polymers -guanidine derivatives, which are known antiseptic agents [42][43][44]. In the case of the latter, close contact of a substance with a high density of positively charged groups with cell walls…”
Section: Discussionsupporting
confidence: 56%
“…Branched oligoguanidines have significantly lower toxicity and pronounced bactericidal and antiviral activities compared with polymer analogs with linear structures [44,45]. This confirms their application potential as active ingredients in the development of antibacterial drugs.…”
Section: Guanidine Derivativesmentioning
confidence: 62%
“…The spectrum of antimicrobial activity of PHMG-HC covers gram-positive and gram-negative bacteria, aerobic and anaerobic bacteria, spore-forming bacteria, mycobacteria, and viruses. Despite its wide spectrum, PHMG-HC is hypoallergenic and has low toxicity [27,28]; it can also be used in conjunction with other biocidal components, e.g., as a skin antiseptic [29,30] or in solid dosage form [31]. The antifungal activity of PHMG-HC enables its application for conservation [32] and as an effective sporicidal tool for combating bacterial spores and nosocomial infections [33].…”
Section: Guanidine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that polycondensation with the formation of branched alkylene guanidine can be effectively conducted at a low optimum temperature [ 17 , 18 ]. Thus, during preliminary tests, it was found that the supply of reagents or their mixtures to the microreactor in the form of concentrated aqueous solutions allows the polycondensation process to be conducted stably, i.e., with a small number of technological failures [ 19 ]. Taking into account a need for the synthesis of new antimicrobial agents on one hand, and the development of a promising method for producing them on the other, the aim of this work was to develop a microreactor method for producing branched oligoguanidines with a narrow molecular-weight distribution.…”
Section: Introductionmentioning
confidence: 99%